Mediating Role of Customer Value Co-creation and Internal Branding Between Brand Orientation and Brand Performance: Moderating Effect of Enterprise Innovative Capabilities-Evidence From Agri Product Users - Yu, Zhifang (Frontiers in Psychology, 2022)
There has been a rejuvenated interest from the researcher and scholars regarding the various ways in which organization can enhance their overall brand performance. Enterprise brand orientation are said to be the main factors that aid in improving brand performance along with internal branding ad the customer value co creation. To assess this relationship, the present study undertook an inquiry to investigate the impact of enterprise brand orientation on brand performance. Moreover, the mediating roles of customer value co creation and internal branding were also studied. Data was obtained from 358 Chinese consumers of various household, electronic, and textile goods through a self-administered survey. A SEM technique was applied using Smart PLS to examine the data. The findings suggested that enterprise brand orientation had a significant effect on brand performance. Moreover, it was also observed that internal branding and customer value co creation also had a predicting role in brand performance. In addition to this, customer value co creation and internal branding were seen to be strongly mediating the relationships between enterprise brand orientation and brand performance. The study also checked the moderating role of enterprise innovative capabilities on the effect on enterprise brand orientation and brand performance. The theoretical implication entailed the value addition made by the current study in expanding the knowledge on the predictors of enterprise brand equity. The practical implication outlined the steps that could be taken by organizations to improve brand performance through enterprise brand orientation; internal branding and customer value co creation so that customer satisfaction and enterprise brand performance could be enhanced.